2007
DOI: 10.1080/13502930701321675
|View full text |Cite
|
Sign up to set email alerts
|

The Music One‐to‐One project: developing approaches to music with parents and under‐two‐year‐olds

Abstract: Detailed analyses of adult-infant interaction among some European and North American populations have revealed that it resides on characteristics such as synchronous timing, phrasing, pitch contours and variations of dynamic intensity that are essentially musical in nature. Moreover, this musicality of infancy is the medium which enables and supports the development of early communication. Observations of practice and interviews with 15 early childhood music practitioners in England suggested that a consensual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Regarding listening behaviours, the findings demonstrate that the mothers listen most to pop and rock music, suggesting that their choice of repertoire may well be driven by their own musical preferences rather than with their infant specifically in mind (see also Young, Street, & Davies, 2007). Indeed, we know that listening to music can regulate aspects of mood and enhance wellbeing (Laukka, 2007;Thoma, Ryf, Mohiyeddini, Ehlert, & Nater, 2012), and it may be that mothers listen to music as a form of 'company' when home alone with infants and/or to increase enjoyment of day-to-day routines.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding listening behaviours, the findings demonstrate that the mothers listen most to pop and rock music, suggesting that their choice of repertoire may well be driven by their own musical preferences rather than with their infant specifically in mind (see also Young, Street, & Davies, 2007). Indeed, we know that listening to music can regulate aspects of mood and enhance wellbeing (Laukka, 2007;Thoma, Ryf, Mohiyeddini, Ehlert, & Nater, 2012), and it may be that mothers listen to music as a form of 'company' when home alone with infants and/or to increase enjoyment of day-to-day routines.…”
Section: Discussionmentioning
confidence: 97%
“…There was evidence from the parents’ comments that music in some homes had become a resource for coping with parenting, for establishing family rituals, such as bedtime (see also Young, 2008), and for some a desire to make music as special for their child as it was to them. Young, Street, and Davies (2007) also found that homes were musically rich environments.…”
Section: Literature Review: What Do Young Children Learn Through Music?mentioning
confidence: 96%
“…These findings build on the current research findings outlining a number of benefits for parents attending music groups, including social support (Barrett, 2009Young, Street & Davies, 2007). Pitt and Hargreaves (2016) suggest socialisation in the music group may be multidimensional, experienced between the parent and their child, and then amongst the wider group (Pitt & Hargreaves, 2016).…”
Section: Theme 4: For Parents To Socialise -Meet New People and Buildsupporting
confidence: 65%